Characterization of a Novel Diarrheagenic Strain of Proteus mirabilis Associated With Food Poisoning in China - Gong, Zelong; Shi, Xiaolu; Bai, Fang; He, Xiaolong; Zhang, Hanyun; Li, Yubin; Wan, Yu; Lin, Yiman; Qiu, Yaqun; Chen, Qiongcheng; Hu, Qinghua; Cao, Hong (Frontiers in Microbiology, 2019)
Proteus mirabilis is commonly considered to be an opportunistic pathogen causing urinary tract infections (UTIs) in humans. However, some strains of P. mirabilis were found to be associated with food-poisoning outbreaks, with the pathogenic mechanism are still unclear. In our study, we described a novel strain of P. mirabilis C02011 isolated from patients’ specimens in a food poisoning in China. In order to determine its gastrointestinal pathogenicity, experiments were performed in comparison with P. mirabilis B02005 strain (isolated from healthy people) and P. mirabilis ATCC 29906 strain both in vitro [Caco-2 cells: bacterial adhesion and invasion assays, giemsa staining and transmission electron microscope (TEM)] and in vivo (BALB/c mice model: fecal character, colon injury, histological examination, immunochemistry and western blotting). According to the results, C02011 strain exhibited almost identical characteristics with B02005 strain in bacterial appearance and proliferation. In vitro, Caco-2 cells were infected with P. mirabilis C02011, B02005 and P. mirabilis ATCC 29906 strains, respectively. After that, giemsa staining and TEM were used for observing the infection process of C02011 strain. Meanwhile, adhesive abilities of different strains were rated as following: P. mirabilis B02005> P. mirabilis C02011> P. mirabilis ATCC 29906 (P<0.01); invasive abilities of different strains were rated as following: P. mirabilis C02011> P. mirabilis B02005> P. mirabilis ATCC 29906 (P<0.01). In vivo, BALB/c mice were infected with P. mirabilis C02011 and B02005 strains respectively. C02011 strain shows more virulent than B02005 strain in term of the following indicators: 1) feces water content and fecal character; 2) colon length of mice; 3) histological examination on mice intestine tissues; 4) ELISA assay for detecting TNF-α level in colon; 5) WB and IHC for detecting occludin protein expression in colon. Based on these results, we firstly validated that the novel strain of P. mirabilis C02011 shows more gastrointestinal pathogenicity comparing with other strain isolated from healthy individual. In addition, type IV secretion system (T4SS) was preliminarily confirmed to play an important role on the pathogenesis of diarrheal P. mirabilis isolated from the food poisoning incident .